Enhancement of surface properties on Low Density Polyethylene packaging films using various fluorination routes. (May 2015) - Peyroux, Jérémy; Dubois, Marc; Tomasella, Eric; Frézet, Lawrence; Kharitonov, Alexander P.; Flahaut, Delphine
Abstract : Graphical abstract: Highlights: Two different fluorination routes were investigated in this work. Mechanisms occurred on the materials were elucidated. Direct fluorination is identified as an efficient way to adjust surface properties. Fluorination using atomic fluorine is an alternative process to improve properties. The pristine polymer surface properties have been successfully enhanced. Abstract: Nowadays, packaging market deployment requires an important attention. Influence of treatment with molecular (F2 ) or atomic (F ) fluorine on properties of Low Density Polyethylene (LDPE) films was investigated. The films were treated using direct fluorination conditions with F2 or a specific reagent XeF2, which releases atomic fluorine F . Changes of LDPE chemical composition were investigated by FTIR and solid state NMR. Surface morphology was studied by several microscopy techniques (SEM and AFM). Finally to further characterize film properties after treatments, surface energy measurements and electron paramagnetic resonance (EPR) analyses were also carried out. An upper fluorinated layer, which contains mainly high amount of CF2, was formed during the direct fluorination conditions (F2 ). For the process performed with XeF2, specific groups CHF were detected not only on the polymer surface but also in the bulk. The final CHF/CF2 ratio depended on the fluorination route. Treatment with F (originated from XeF2 decomposition) resulted in CHF groups in bulk prevailing formation whereas F2 formed mainly CF2 groups. Regardless to the reactive species, radicals (dangling bonds) appeared during the fluorination and reacted with oxygen during the exposition to air after the treatment. Such a process resulted in oxygenated polar groups formation and consequently in the surface energy increase.